Investigation into the integration of ICT in the teaching and learning of geography in secondary schools in Nkhotakota district, Malawi - Banda, Aulaya James (Mzuzu University, 2023)
Technology has become essential in education world over. Integration of ICT in education has improved the quality of education and academic performance. Consequently, this study sought to investigate the extent of ICT integration in the teaching and learning of Geography in secondary schools of Nkhotakota district, Malawi. The objectives of the study were: to assess the adequacy of ICT resources for teaching and learning Geography in secondary schools; to examine the attitude of teachers in the integration of ICT in the teaching and learning of Geography in secondary schools; and to investigate the extent to which ICT is integrated in the teaching and learning of Geography. The study was guided by Roger's Theory of Diffusion of Innovations model and was carried out in secondary schools in Nkhotakota, Malawi. A descriptive survey research design was used, and the study targeted 12 secondary schools. Through, Purposive and simple random sampling technique, a sample of 12 secondary schools from Nkhotakota district. 12 school Head teachers, 36 Geography teachers, the DEM and 240 forms 1 to 4 students were sampled for the study. Questionnaires, interview and observation schedules were used as instruments for data collection. The quantitative data for the study were analyzed using Statistical Package for Social Sciences (SPSS) and Microsoft Word. The qualitative data obtained from the open-ended questions were analyzed thematically based on research objectives. This study has established that ICT resources are inadequate in the school; schools lack power supply; internet connectivity; schools lack ICT policy. However, the study has established that teachers have positive attitude towards ICT integration in education despite a number of them lacking training in ICT. Consequently, the study recommends for provision of ICT resources and training of Geography teachers in ICT.